Artificial intelligence-assisted assessment of metabolic response to tebentafusp in metastatic uveal melanoma: a long axial field-of-view (18F)FDG PET/CT study - Sachpekidis, Christos; Machiraju, Devayani; Strauss, Dimitrios; Pan, Leyun; Kopp-Schneider, Annette; Edenbrandt, Lars; Dimitrakopoulou-Strauss, Antonia; Hassel, Jessica C. (European journal of nuclear medicine and molecular imaging, 2025)
Tebentafusp has emerged as the first systemic therapy to significantly prolong survival in treatment-naïve HLA-A*02:01 + patients with unresectable or metastatic uveal melanoma (mUM). Notably, a survival benefit has been observed even in the absence of radiographic response. This study aims to investigate the feasibility and prognostic value of artificial intelligence (AI)-assisted quantification and metabolic response assessment of [18F]FDG long axial field-of-view (LAFOV) PET/CT in mUM patients undergoing tebentafusp therapy.
Im Titel erscheint "18F" in eckigen Klammern, die 18 ist dabei hochgestellt
Gesehen am 29.01.2026